Aprendizagem significativa e rotação por estações: o que pode nos auxiliar no ensino de física? - Lorensi, Angela Maria Dalla Rosa (2024)
The main basis of this work is the application of the active methodology station rotation, for high school students. The objective is to use meaningful learning in the process of acquiring new knowledge, related to concepts of Physics. It is a proposal that had David P. Ausubel's Cognitivist learning theory as its main learning theory. In order to facilitate this aim, the station rotation was applied to a 2nd grade high school class, at a public school in the state of Paraná in 2022. The total number of classes to implement the educational product is 5 classes of 50 minutes each one. To begin the proposal before the classroom, students were asked to carry out a bibliographical research about the heat transmission processes: conduction, convection and irradiation. Afterwards, a pre-test was administered to verify prior knowledge so that we could make use of the subsumers brought by the students. The methodology was applied in accordance with expectations and after implementing the station rotation methodology proposal, a post-test was applied and analyzing the data, these showed much more than signs of significant learning, we observed that the students were evolved by educational and life experience. They were introduced to a new teaching methodology, which many were not familiar with, and when asked if they would be willing to undertake new activities similar to this, they almost unanimously said yes. This research was exploratory, with a case study method, in which the data collection technique was used through questionnaires and quantitative data analysis, as well as discussion based on literature and in the author's experience of more than twenty years of teaching. The application of the active station rotation methodology proved to be a broad tool that can be explored in different ways. For example, with different numbers of students and stations, new practices and using the resources that each teacher and school have, within their limitations. After analyzing and discussing the results, we can conclude that this proposal and the material that was developed can be successfully replicated.